Effectiveness of early treatment with plasma exchange in patients with Stevens–Johnson syndrome and toxic epidermal necrolysis - Atsushi Senda; Kiyohide Fushimi (Scientific Reports, 2024)
Abstract Stevens–Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) are potentially fatal medical conditions that lack established treatment. Therapeutic plasma exchange (PE) is a potential treatment option; however, its effectiveness is unclear. We aimed to evaluate the effectiveness of PE in patients with SJS/TEN. A retrospective cohort study was conducted using data from the Japanese National Administrative Claims database from 2016 to 2021. The analysis included 256 patients diagnosed with SJS/TEN who were admitted to the intensive care unit, of whom 38 received PE and 218 did not. The outcomes of patients who did and did not receive PE within the first 24 h of admission were compared. The risk ratios and 95% confidence intervals of the PE group compared with those of the no-PE group were as follows: in-hospital mortality, 0.983 (0.870–1.155); 30-day mortality rate, 1.057 (0.954–1.217); 50-day mortality rate, 1.023 (0.916–1.186); and length of hospital stay, 1.163 (0.762–1.365). This study does not provide evidence of a benefit of PE in reducing mortality or length of hospital stay in patients with severe SJS/TEN.